Odpowiedź:
5.
A. = 3x² - xy
B = -2y
C = 3x
a)
(A * B) * C = (3x² - xy)(-2y) * 3x = (-6x²y + 2xy²) * 3x = -18x³y + 6x²y²
b)
A * (B * C) = (3x² - xy)(-2y * 3x) = (3x² - xy)(-6xy) = -18x³y + 6x²y²
c)
(A + B) * C = (3x² - xy - 2y) * 3x = 9x³ - 3x²y - 6xy
d)
A * C + B * C = (3x² - xy) * 3x + (-2y) * 3x = 9x³ - 3x²y - 6xy
9.
a)
3(x² - 2x + 3) - 2(x² - 5x - 1) = 3 * 2² - 6 * 2 + 9 - 2 * 2² + 5 * 2 + 2 =
= 3 * 4 - 12 + 9 - 2 * 4 + 10 + 2 = 12 - 3 - 8 + 12 = 9 + 4 = 13
b)
(2ab + b) - b(a - 2ab + a²) = -2 * 0,1 * 10 - 10 + 10(0,1 + 0,1 + 2 * 0,1 * 10 + 0,01) =
= -2 - 10 + 10(0,2 + 2 + 0,1) = -12 + 10 * 2,3 = -12 + 23 = 11
a = 0,1
b = -10
dla x = 2
Szczegółowe wyjaśnienie: